Social marketing interventions: insights from a system dynamics simulation model - Saunders, Stephen Graham; Truong, V. Dao (Journal of social marketing, 2019)
Purpose The purpose of this paper is to explore the dynamic nature of behaviour change over time and to gain insights into the effectiveness of social marketing efforts at three different intervention points under three different delay time conditions. Design/methodology/approach A system dynamics simulation modelling approach was used. Findings The findings showed that the effectiveness of social marketing interventions at different points of intervention and delay times is dependent on complex dynamic system interactions and feedback loops. Research limitations/implications As the dynamic simulation model was an abstraction or simplified representation, it was only useful to gain insights into generalised patterns of behaviour over time. Practical implications The paper provided practical guidance to social marketers’ intent on gaining insights into “where to do” and “when to do” social marketing rather than “how to do” social marketing. Originality/value The paper provided theoretical and practical insights into the temporal nature of behaviour change and the effectiveness of social marketing interventions in influencing behaviour over time.